Paclitaxel synergizes with exposure time adjusted CD22-targeting immunotoxins against B-cell malignancies - Müller, Fabian; Stookey, Stephanie; Cunningham, Tyler; Pastan, Ira (Oncotarget, 2017)
CD22-targeted recombinant immunotoxins (rIT) are active in hairy cell leukemia or acute lymphoblastic leukemia (ALL), but not in mantle cell lymphoma (MCL) patients. The goal was to enhance rIT efficacy in vivo and to define a strong combination treatment. Activity of Moxetumomab pasudotox (Moxe) and LR combined with paclitaxel was tested against MCL cell lines in vitro and as bolus doses or continuous infusion in xenograft models. In the KOPN-8 ALL xenograft, Moxe or paclitaxel alone was active, but all mice died from leukemia; when combined, 60% of the mice achieved a sustained complete remission. Against MCL cells in vitro, LR was more active than Moxe and the cells had to be exposed to rIT for more than 24 hours for them to die. To maintain high blood levels in vivo, LR was administered continuously by 7-day pumps achieving a well-tolerated steady plasma concentration of 45 ng/ml. In JeKo-1 xenografts, continuously administered LR was 14-fold more active than bolus doses and the combination with paclitaxel additionally improved responses by 135-fold. Maintaining high rIT-plasma levels greatly improves responses in the JeKo-1 model and paclitaxel substantially enhances bolus and continuously infused rIT, supporting a clinical evaluation against B-cell malignancies.
EVALuna2:25765